(+)‐Valencene production in Nicotiana benthamiana is increased by down‐regulation of competing pathways. Issue 1 (18th September 2014) - Cankar, Katarina; Jongedijk, Esmer; Klompmaker, Martin; Majdic, Timotej; Mumm, Roland; Bouwmeester, Harro; Bosch, Dirk; Beekwilder, Jules
Abstract Plant sesquiterpenes, such as (+)‐valencene, artemisinin, and farnesene are valuable chemicals for use as aromatics, pharmaceuticals, and biofuels. Plant‐based production systems for terpenoids critically depend on the availability of farnesyl diphosphate (FPP). Currently, these systems show insufficient yields, due to the competition for FPP of newly introduced pathways with endogenous ones. In this study, for the first time an RNAi strategy aiming at silencing of endogenous pathways for increased (+)‐valencene production was employed. Firstly, a transient production system for (+)‐valencene in Nicotiana benthamiana was set up using agroinfiltration. Secondly, silencing of the endogenous 5‐epi‐aristolochene synthase (EAS) and squalene synthase (SQS) that compete for the FPP pool was deployed. This resulted in a N. benthamiana plant that produces (+)‐valencene as a prevalent volatile with a 2.8‐fold increased yield. Finally, the size of the FPP pool was increased by overexpression of enzymes that are rate‐limiting in FPP biosynthesis. Combined with silencing of EAS and SQS, no further increase of (+)‐valencene production was observed, but emission of farnesol. Formation of farnesol, which is a breakdown product of FPP, indicates that overproducing sesquiterpenes is no longer limited by FPP availability in the cytosol. This study shows that metabolic engineering of plants can effectively be used for increased production of desired products in plants.